Enhancing Science Learning Outcomes with SITAYA Miniature Media: A Quantitative Study of Elementary Education - Praramdana, Gilang Krispiyadi; Hamdan, Hamdan; Gunawan, Agus; Hijriani, Fauziah Dwi (Jurnal Pendidikan Sains, 2024)
This study investigates the impact of SITAYA Miniature media on the learning outcomes of grade VI students in science subjects at SDN 2 Darma. Conventional teaching methods, often less engaging for students, were identified as a significant factor contributing to low academic performance. The study employed a quantitative research approach, with a randomized sample of 43 students divided into an experimental group (24 students) and a control group (19 students). Pretest and posttest data were collected using a structured test instrument, and statistical analyses, including normality, homogeneity, t-tests, and N-Gain tests, were conducted to assess the effectiveness of SITAYA Miniature media. The results showed that the experimental group, which utilized the SITAYA Miniature media, experienced a substantial increase in their posttest scores, with an average of 79.58, compared to the control group’s average of 59.73. The variance in scores also decreased in the experimental group, indicating a more consistent improvement in student understanding. Statistical tests confirmed the significant impact of the SITAYA Miniature media on enhancing student learning outcomes. The findings underscore the importance of innovative educational tools in improving student engagement, understanding, and overall academic performance in science education. While the study is limited by its small sample size and specific context, the results suggest that SITAYA Miniature media could play a crucial role in reshaping science education. Future research should explore its broader applicability and long-term effects across diverse educational settings.DOI: 10.17977/jps.v12i42024p146